2017
DOI: 10.1016/j.neuroscience.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of stem cell transplantation for reflex hypersensitivity after spinal cord injury

Abstract: Stem cells have been used in novel therapeutic strategies for spinal cord injury (SCI), but the effect of stem cell transplantation on neuropathic pain after SCI is unclear. The current meta-analysis evaluates the effects of stem cell transplantation on neuropathic pain after SCI. We first conducted online searches of PubMed, Web of Science, China Academic Journals Full-text Database, and Wanfang Data for randomized controlled trials that compared stem cell transplantation and vehicle treatments in rodent mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Most basic researches and clinical trials also demonstrate that various cell types are generally feasible, but there still remains controversy exists due to significant heterogeneity, leaving us indeterminacy whether cell remedy possesses inherent merits in ameliorating patient's prognosis. After retrieving and reviewing the literature, especially in systematic review and meta-analysis, there are 11 articles including 3 clinical (1 BMSC, 1 OEC, 1 stem cell) [17,18] and 8 animal experiments (2 OEC, 1 BMSC, 3 stem cells, 1 SC, 1 NS/PC) [19][20][21][22][23][24][25][26][27]. However, most of the studies centering on a unitary cell type or self-control failure to provide us the comprehensive and detailed understanding of cell therapy, for example, whether different cell lines generate equivalent clinical outcome, what is the optimum time for cellular therapy, how many cells are suitable for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Most basic researches and clinical trials also demonstrate that various cell types are generally feasible, but there still remains controversy exists due to significant heterogeneity, leaving us indeterminacy whether cell remedy possesses inherent merits in ameliorating patient's prognosis. After retrieving and reviewing the literature, especially in systematic review and meta-analysis, there are 11 articles including 3 clinical (1 BMSC, 1 OEC, 1 stem cell) [17,18] and 8 animal experiments (2 OEC, 1 BMSC, 3 stem cells, 1 SC, 1 NS/PC) [19][20][21][22][23][24][25][26][27]. However, most of the studies centering on a unitary cell type or self-control failure to provide us the comprehensive and detailed understanding of cell therapy, for example, whether different cell lines generate equivalent clinical outcome, what is the optimum time for cellular therapy, how many cells are suitable for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The SYRCLE's tool, based on the Cochrane Collaboration RoB Tool, aims to assess methodological quality and has been adapted to aspects of bias and plays a role in animal experiments ( 27 ). However, several previous meta-analyses of cell transplantation to alleviate neuropathic pain have not analyzed RoB based on the SYRCLE's tool ( 19 , 46 , 47 ). Another systematic review evaluated the therapeutic potential of regulatory T lymphocytes in periodontitis animal models and rated 42.11% of projects as unclear RoB ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of GABAergic neuron function therefore plays an important role in the treatment of pain. It was reported that stem cell transplantation could supplement the inhibitory interneurons in the CNS, restore the function of GABA neurons, and inhibit the mechanical hypersensitivity reaction (19). GABAergic neurons or neural progenitor cells (NPCs) may have similar potential to improve neuropathic pain in SCI or PNI models (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…For the mice, improvement in thermal withdrawal latency was observed. However, no improvement was seen in rat studies [72]. In a rat spinal cord hemisection model, BMSCs were noted to promote astrocyte migration to the injury epicenter.…”
Section: Intravenous Deliverymentioning
confidence: 93%